Comparison of in vitro properties of periodontal ligament stem cells derived from permanent and deciduous teeth - Masoumeh Khoshhal; Iraj Amiri; Leila Gholami (Tabriz University of Medical Sciences, 2017)
Background. Stem cells have contributed to the development of tissue-engineered-based regenerative periodontal therapies. In order to find the best stem cell sources for such therapies, the biologic properties of stem cells isolated from periodontal ligaments (PDL) of deciduous (DePDLSC) and permanent (PePDLSC) teeth were comparatively evaluated. Methods. PDL stem cells were isolated from six sound fully erupted premolars and six deciduous canines of healthy subjects. In vitro biologic characteristics such as colony formation, viability, stem cell marker identification and osteogenic differentiation (using alkaline phosphatase analysis and Alizarin red staining) were comparatively assessed using one-way ANOVA and post hoc Tukey tests using SPSS 13.0. Results. Stem cell populations isolated from both groups were CD105+ and CD90+ and CD45‒. No statistically significant differences were found in stem cell markers, colony formation and viability. Both groups were capable of osteogenic differentiation. However, alkaline phosphatase activity test showed a statistically significant difference, with PePDLSC exhibiting higher alkaline phosphatase activity (P=0.000). No statistically significant difference was seen in quantitative alizarine red staining (P=0.559). Conclusion. Mesenchymal stem cells of PDL could successfully be isolated from permanent and deciduous teeth. A minor difference was observed in the osteogenic properties of the two cell types, which might affect their future clinical applications.